Can Organizational Conflict and Work Stress Improve Teacher Performance During Pandemic? - Nurlaili Nurlaili (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
The COVID-19 pandemic changed teachers' habits in teaching, from offline to online methods, causing various problems resulting in organizational conflicts and work stress, which further affected teacher performance. This study aims to determine the level of organizational conflict, work stress, and teacher performance, as well as the influence of organizational conflict and work stress on teacher performance during the Covid-19 pandemic. The research method used is quantitative, with data collection techniques through questionnaires and interviews. Data analysis uses multiple linear regression. The results showed that: Most teachers experience organizational conflicts, work stress, and teacher performance at a moderate level. There is a positive influence of organizational conflict and work pressure on teacher performance, which means that organizational conflict and work stress improve teacher performance during the Covid-19 pandemic.  The results of this study are helpful in the field of school management, which shows the importance of professionalism, communication, and good cooperation to resolve organizational conflicts and work pressures, so that teacher performance improves.